Update of mutations in the genes encoding the pancreatic beta-cell K(ATP) channel subunits Kir6.2 (KCNJ11) and sulfonylurea receptor 1 (ABCC8) in diabetes mellitus and hyperinsulinism. - Flanagan, SE; Clauin, S; Bellanné-Chantelot, C; de Lonlay, P; Harries, L; Gloyn, A; Ellard, S (2009)
The beta-cell ATP-sensitive potassium (K(ATP)) channel is a key component of stimulus-secretion coupling in the pancreatic beta-cell. The channel couples metabolism to membrane electrical events bringing about insulin secretion. Given the critical role of this channel in glucose homeostasis it is therefore not surprising that mutations in the genes encoding for the two essential subunits of the channel can result in both hypo- and hyperglycemia. The channel consists of four subunits of the inwardly rectifying potassium channel Kir6.2 and four subunits of the sulfonylurea receptor 1 (SUR1). It has been known for some time that loss of function mutations in KCNJ11, which encodes for Kir6.2, and ABCC8, which encodes for SUR1, can cause oversecretion of insulin and result in hyperinsulinism of infancy, while activating mutations in KCNJ11 and ABCC8 have recently been described that result in the opposite phenotype of diabetes. This review focuses on reported mutations in both genes, the spectrum of phenotypes, and the implications for treatment on diagnosing patients with mutations in these genes.